Multi-modal cross-linguistic perception of Mandarin tones in clear speech - Zeng, Yuyu; Leung, Keith K. W.; Jongman, Allard; Sereno, Joan A.; Wang, Yue (Frontiers in Human Neuroscience, 2023)
Clearly enunciated speech (relative to conversational, plain speech) involves articulatory and acoustic modifications that enhance auditory-visual (AV) segmental intelligibility. However, little research has explored clear-speech effects on the perception of suprasegmental properties such as lexical tone, particularly involving visual (facial) perception. Since tone production does not primarily rely on vocal tract configurations, tones may be less visually distinctive. Questions thus arise as to whether clear speech can enhance visual tone intelligibility, and if so, whether any intelligibility gain can be attributable to tone-specific category-enhancing (code-based) clear-speech cues or tone-general saliency-enhancing (signal-based) cues. The present study addresses these questions by examining the identification of clear and plain Mandarin tones with visual-only, auditory-only, and AV input modalities by native (Mandarin) and nonnative (English) perceivers. Results show that code-based visual and acoustic clear tone modifications, although limited, affect both native and nonnative intelligibility, with category-enhancing cues increasing intelligibility and category-blurring cues decreasing intelligibility. In contrast, signal-based cues, which are extensively available, do not benefit native intelligibility, although they contribute to nonnative intelligibility gain. These findings demonstrate that linguistically relevant visual tonal cues are existent. In clear speech, such tone category-enhancing cues are incorporated with saliency-enhancing cues across AV modalities for intelligibility improvements.